Towards a Theory of Prose - Brelsford, Joanne (My University, 1968)
A critical analysis of several approaches to prose, and an attempt to construct a theory of prose as art, on which a language of prose criticism might be based.
Keywords: Prose; Prose Criticism; Art Criticism